Industrial Applications Of Red Pigment Prodigiosin Extracted From Serratia Marcescens (Applied Biological Research, 2023)
In present study, the industrial applications of red pigment prodigiosin,  extracted from Serratia marcescens, were explored. Twelve textile fabric samples  (santoon, georgette, bubble, cotton 20/20, cotton polyester, lycra, butter crape, hosiery, satin, linen, cotton and polyester) were used to check the fabrics staining  potential of prodigiosin under acidic, basic and neutral conditions. Out of the  selected fabrics, the pigment gave attractive red shade to bubble, hosiery, cotton  20-20 and lycra in all the sets. Colour intensity decreased in santoon, cotton  polyester, cotton and polyester. Very faint colouration was noticed in satin, linen,  butter crape and georgette. Application of prodigiosin as food colorant in bakery  products revealed successful use of pigment in decoration of cakes and other  bakery products. Different concentrations (1:1 and 1:2) of pigment were used in  paper making process. The products were exposed to sunlight and fluorescent  light for 4 h in which sunlight caused higher fading effect. Prodigiosin was also  used in soap making at 1, 2 and 3 mg L-1concentration and it gave attractive  colour shades to the final products. For candle making, different concentrations  (1:5, 2:5 and 3:5) of pigment used were and the study showed that the prodigiosin  can be an attractive choice for making colourful candles of different shapes. The  potential of prodigiosin as ink for highlighter pen was tested by preparing  different compositions in presence of citric acid and glycerol. Results suggested  that the concentration >0.25% can be readily used in highlighter pen.
Keywords: Bakery industry; paper industry; prodigiosin; Serratia marcescens; textile industry